Evaluasi Pelaksanaan Kebijakan Insentif Fiskal Kendaraan Bermotor - Rebecca Yolanda Artha Uli; Siti Nuryanah (Jurnal Ilmiah Wahana Pendidikan, 2023)
Tax amnesty is a policy provided by the government to encourage taxpayer compliance in carrying out their tax obligations so that it will increase regional income, especially from the Motor Vehicle Tax sector so that the Regional Revenue and Expenditure Budget is more sustainable. However, it is feared that the amnesty provided by the Regional Government in the form of fiscal incentives each year will have a negative effect in the long run. The purpose of this research is to evaluate the tax amnesty policy in terms of the write-off of Motor Vehicle Tax at the DKI Jakarta Provincial Government level based on William N. Dunn's (2003) evaluation theory with 6 (six) criteria namely Effectiveness, Efficiency, Adequacy, Alignment, Responsiveness and Accuracy Program. Evaluation is also carried out by looking at the problems faced by Bapenda as a regulator in collecting Motor Vehicle Tax which causes delays in the provision of incentives. The research used triangulation through analysis of Bappenda documents in 2017 - 2021 and will be validated using interview techniques with Bapenda and Samsat officers. The results showed that on average the provision of PKB incentives every year by the Government of DKI Jakarta was good enough to be given, judging from the achievement of the goal of providing the program, namely to support the achievement of PKB revenue from what had been targeted at the beginning of the period. However, there are still problems that need to be fixed.